The STAT3-VDAC1 axis modulates mitochondrial function and plays a critical role in the survival of acute myeloid leukemia cells - Kellen B. Gil; Jamie Borg; Rosana Moreira Pereira; Anagha Inguva-Sheth; Geovana Araujo; Jeremy Rahkola; William Showers; Abby Grier; Angelo D’Alessandro; Clayton Smith; Christine McMahon; Daniel A. Pollyea; et al. (Haematologica)
Signal transducer and activator of transcription 3 (STAT3) is a well-described transcription factor that mediates oxidative phosphorylation and glutamine uptake in bulk acute myeloid leukemia (AML) cells and leukemic stem cells (LSCs). STAT3 has also been shown to translocate to the mitochondria in AML cells, and phosphorylation at the serine 727 (pSTAT3 S727) residue has been shown to be especially important for STAT3’s mitochondrial functions. We demonstrate that inhibition of STAT3 results in impaired mitochondrial function and decreased leukemia cell viability. We discovered a novel interaction of STAT3 with voltage-dependent anion channel 1 (VDAC1) in the mitochondria which provides a mechanism through which STAT3 modulates mitochondrial function and cell survival. Through VDAC1, STAT3 regulates calcium and oxidative phosphorylation in the mitochondria. STAT3 and VDAC1 inhibition also result in significantly reduced engraftment potential of LSCs, including primary samples resistant to venetoclax. These results implicate STAT3 as a therapeutic target in AML.